Influence of spiritual characteristics of intelligence, emotional intelligence and personality type towards the attitude of the post-transformation of Stain Jurai Siwo Metro become Iain Metro - Syukron, Buyung; Soehardi, Dwi Vita Lestari (Universitas Islam Negeri Raden Intan Lampung, 2020)
One of the important dimensions and aspects that are the key to addressing the needs of the role and function of democracy is to seek change or transformation of forms, systems and institutional structures. The purpose of this study was to determine the characteristics of the respondent (lecturer) which correlated with the type of Spiritual Intelligence, Emotional Intelligence and the type of personality possessed by perceptual lecturers in the transformation process of STAIN Jurai Siwo Metro into IAIN Metro. This type of research is quantitative. The nature of the research emphasizes numerical data (numbers) processed by statistical methods. While the research approach is carried out by describing the ex post facto. For data processing techniques using validity and reliability tests using the product-moment formula. The data analysis used in this research is the univariate analysis test, multivariate analysis test, classical assumption test, hypothesis test, and direct and indirect effect test. The results showed that the attitude of the lecturers influenced the transformation of STAIN Jurai Siwo Metro into IAIN Metro. The attitude of the lecturer towards the post-transformation process of STAIN Jurai Siwo Metro into IAIN Metro is a conflicting dysfunctional behaviour, covering several interconnected aspects, namely cognitive, affection, and behaviour which are influenced by various factors.